Practically applicable water oxidation electrodes from 3D-printed Ti6Al4V scaffolds with surface nanostructuration and iridium catalyst coating - Hofer, André; Wachter, Sebastian; Döhler, Dirk; Laube, Armin; Sánchez Batalla, Beatriz; Fu, Zongwen; Weidlich, Claudia; Struckmann, Thorsten; Körner, Carolin; Bachmann, Julien (Electrochimica Acta, 2022)
This study establishes the applicability of 3D printing (additive manufacturing) towards the generation of titanium alloy scaffolds for water oxidation electrodes. The scaffolds can be subsequently nanostructured by electrochemical anodization to enhance their surface area and coated with iridium as the electrocatalyst. We focus on the characterization of the functional electrodes in process-relevant conditions (1 M HSO, 60 C, stirring) in terms of their performance and stability in a holistic manner. Various preparative conditions yield various patterns of performance and stability, as quantified by overpotentials in steady-state electrolyses, maximum current densities in dynamic voltammetry, surface roughness rf, and by overpotential increase, iridium loss, and decrease after 100 h of operation, on the other hand. In other words, the system is highly flexible and can be adapted to specific constraints depending on the application chosen.<br
Keywords: ALD; Electrochemistry; Heterogeneous catalysis; Iridium; Water splitting